Nerve Ultrasound, Electrophysiological, and Clinical Changes in Treatment-Naive Chronic Inflammatory Demyelinating Polyneuropathy: A Case Report. Issue 1 (January 2019) - Sato, Takeo; Terasawa, Yuka; Higa, Hitomi; Matsuno, Hiromasa; Arai, Ayumi; Omoto, Shusaku; Mitsumura, Hidetaka; Toyoda, Chizuko; Koike, Haruki; Iguchi, Yasuyuki
Abstract : Summary: We report the case of a 74-year-old woman with treatment-naive chronic inflammatory demyelinating polyneuropathy evaluated by both nerve conduction studies and nerve ultrasound (NUS) before and after initial treatment. Performing both nerve conduction study and NUS before and after initial treatment seems rare for treatment-naive chronic inflammatory demyelinating polyneuropathy. This case yielded two major findings. First, improvement of nerve swelling as evaluated by NUS correlated well with the improvement of neurological symptoms. Second, NUS improvements were seen right after treatment, whereas electrophysiological improvements were not. Nerve ultrasound might thus allow for judgment of curative effects much more immediately and sensitively than nerve conduction study in treatment-naive chronic inflammatory demyelinating polyneuropathy.